PENGARUH E-SERVICE QUALITY DAN KEMUDAHAN TERHADAP NIAT BELI ULANG DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi Pada Pengguna Jasa Uber Motor di Surabaya) - DIYANPUTRA PRADANA, MUH. (Jurnal Ilmu Manajemen (JIM), 2018)
Now days an internet technology usage more valuable in many aspect, mainly in the business world. An internet technology access is an innovative way to do company activities on online market that called by electronic business and commerce (e-bussiness and e-commerce). The phenomenal of research showed that motor Uber as follower or pioneer online transportation namely Go-jek. The conclusion is uber bike is new more comparative than Go-jek that became pioneer online transportation in Indonesia had shown by customer who ordered online transportation in the Uber Motor more easily also the service is more faster. Beside that the cost cheapest so the people can use it than by using Gojek. The type of this research that used in this research is conclusive research. The respondent on this research is in the Surabaya. The respondent who had been on this research is 220 and maximum age is 48 years who know and ever order uber motor online on last two week. The instrument of research that used is questionnaire, and then the data will be input by using path analysis. In addition, the result has shown that E-Service quality more influence to repurchase intention and satisfaction. Satisfaction variable is influence to repurchase intention and satisfaction on uber motor user in Surabaya. Keywords: E-service quality, Ease of use, Repurchase Intention, Satisfaction